2017
DOI: 10.1002/er.3779
|View full text |Cite
|
Sign up to set email alerts
|

A novel intersectant flow field of metal bipolar plate for proton exchange membrane fuel cell

Abstract: Summary A novel intersectant flow field of metal bipolar plate for proton exchange membrane fuel cell (PEMFC) was proposed. The bionics, fractal theory, and Murray's law were employed to design the novel flow field to decrease the drag force for the reaction medium and product. Computational fluid dynamics method was employed to investigate the performance of the novel flow field. The performance of traditional serpentine flow field was compared with the said one to calibrate the efficiency of the novel design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 17 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…Recently a non-rectangular intersectant geometry ( Figure 5D) has been tested based on a theoretical model and on the experimental setup for a metallic FFP (Dong-Hui et al, 2017. The optimal dimensions and porosity per unit length were determined as 0.6 × 0.3 mm and 0.5, respectively.…”
Section: Mesh-type Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently a non-rectangular intersectant geometry ( Figure 5D) has been tested based on a theoretical model and on the experimental setup for a metallic FFP (Dong-Hui et al, 2017. The optimal dimensions and porosity per unit length were determined as 0.6 × 0.3 mm and 0.5, respectively.…”
Section: Mesh-type Designmentioning
confidence: 99%
“…A similar approach was proposed to deal with suspensions of micro-and nanoparticles in rigid and compliant ducts (Barber and Emerson, 2008;Kizilova et al, 2012;Cherevko and Kizilova, 2017). An improved intersectant design (Figure 5D) with the cross-sectional angles computed according to Murray's formula (7) was studied by CFD and validated experimentally (Dong-Hui et al, 2017). The design showed better performance, more uniform distribution of reactants and better water removal.…”
Section: Bio-mimetic Designs For Ffpmentioning
confidence: 99%
“…2,3 As shown in Figure 1, flow channels formed on the BPPs play important roles in the stack operation such as water management, reactant distribution, and transport, and thus influencing the output performance of fuel cells. 4 For conventional carbon-based BPPs, various configurations and section shapes of the flow channel were proposed to eliminate technical issues such as uneven flow distribution and water flooding during the cell operation. For example, Kumar et al 5 reported that the optimum channel width, rib width, and channel depth were close to values of 1.5, 0.5, and 1.5 mm, respectively, to obtain better fuel cell performance and higher hydrogen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve commercial deployment of the fuel cell, thin metallic BPPs are widely used to replace traditional graphite BPPs by virtue of their good mechanical properties, electrical conductivity, high productivity, and low cost in mass production . As shown in Figure , flow channels formed on the BPPs play important roles in the stack operation such as water management, reactant distribution, and transport, and thus influencing the output performance of fuel cells …”
Section: Introductionmentioning
confidence: 99%
“…Suresh and Jayanti presented detailed analysis of cross‐flow in the GDL through computational fluid dynamic (CFD) simulations and quantified the cross‐flow using Peclet number. Dong‐Hui et al suggested a new flow design named as novel intersectant flow field using bionics, fractal theory, and Murray's law to reduce the drag force for product and reaction medium. They showed improved performance with their design against single serpentine design.…”
Section: Introductionmentioning
confidence: 99%